Cluster-Based Industrial Parks : A Practical Framework for Action - Monga, Célestin (2012)
They are being hailed as the new Holy Grail of economic development. The success of special economic zones (SEZ) in general and specialized ones in particular (industrial and technology parks) in countries as diverse as Australia, Denmark, Sweden, Germany, Switzerland, Ireland, Japan, the United Kingdom, the United States, and more recently, China; Korea; Taiwan, China; or Mauritius, has led several African leaders to launch new similar initiatives. This paper establishes a common point of reference for those who believe in the virtues of SEZs, explains why the many existing ones have not delivered the expected outcomes, and summarizes the key issues on the agenda. It then suggests cluster-based industrial parks as the most effective tool for developing competitive industries and generating employment, and provides some practical guidance to development practitioners and policymakers on the road ahead.